The Embodiment of Global Governance Through Hexahelix in Preserving Terracotta Architecture - Khaerul Umam; Feni Astuti (Iapa Proceedings Conference, 2022)
Terracotta is a culture that emphasizes the unification of natural elements with human life. In this case, humans should preserve what has been given by God in the form of the universe, which humans can then reuse. As part of the culture and architectural concept, the part often discussed by researchers in various scientific articles leads to terracotta as an art or architectural concept. This is also the concern of researchers in this study. This research aims to analyze the realization of Global Governance through the actors who are members of the hexahelix in preserving terracotta architecture. Furthermore, this research is a descriptive study with a qualitative approach, while data collection techniques are carried out through observation, interviews, FGDs, and literature studies. The results showed that government actors, academics, and the community had the most significant roles in preserving terracotta architecture in Majalengka Regency.